Determine Eimeria Stiedae Immunogenic Antigens in Sonicated Sporulated Oocyst Vaccine in Rabbits (Journal of Hama University, 2022)
The result of study showed the possibility of detection the most important immunogenic antigens from sonicated sporulated oocyst vaccine, which are responsible of antibody production after experimental infection.After isolation and sporulation of oocysts from liver, then subjected to ultra-sonication using an Ultrasonic Homogenizer. Then applying Western Blotting technique (to detect the most important immunogenic antigens using collected serum from infected rabbits (day 14 post challeng ) with protein extract of the sonicated sporulated oocyste, the results showed nine bands of antigens with immunogenic capacity, whose molecular weights reached (24-26-28-39-57-66-84-119-124) kDa. Three of them are highly colored and have molecular weights: (28, 26 and (24) kDa. The strongest of these was the 28 kDa band, which appeared immediately after application of the reaction substrate and was the thickest.